Unsteady Nanofluid Flow Over Exponentially Stretching Sheet with Vertical Throughflow - Al-Yaari, A. (Springer Science and Business Media B.V., 2021)
Owing to its excellent thermal conductivity, the use of nanofluid as a heat transfer agent has become more popular recently. The study of heat transfer is critical in keeping up with the rapid development of industries such as cooling and advanced the nuclear technology. The purpose of this research is to investigate the unsteady flow, heat, and mass transfer of nanofluid over exponentially stretching sheet. This research's mathematical model manages the nanoparticles passively at the boundary, rather than actively making it physically more realistic. A convective term is also added to the energy equation due to the vertical throughflow. The system of partial differential equations is reduced to nonlinear ordinary differential equations using similarity transformation and then solved using bvp4c solver in MATLAB numerically. The skin friction coefficient, heat transfer rate, velocity, temperature, and nanoparticle volume fraction are computed for various values of relevant parameters involved. Results show that the Brownian motion parameter has no effect on the heat transfer rate. The reduced Nusselt number shows decreasing trend for the thermophoresis parameter and Scmidt number but increases for Prandtl number. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.